1984
DOI: 10.1111/j.1479-828x.1984.tb01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Pregnancy

Abstract: A retrospective study of 75 pregnant epileptic women compared with a parity, age and socioeconomic matched control group of women is presented. Deterioration of control of epilepsy during pregnancy occurred in 24% of women. Statistically significant obstetric complications noted were anaemia, premature labour, premature rupture of the membranes and postpartum haemorrhage. There was 2.5-fold increase in the incidence of congenital anomalies in the neonates, an increase in feeding difficulties and a reduced inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…There have been conflicting results in previous studies regarding epilepsy and preterm delivery. Some studies have reported an increased risk 9,10 and others have not 11–14 . Most studies of epilepsy and pregnancy outcome have failed to report on duration of gestation, and methods of estimating gestational age have been described in few studies.…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting results in previous studies regarding epilepsy and preterm delivery. Some studies have reported an increased risk 9,10 and others have not 11–14 . Most studies of epilepsy and pregnancy outcome have failed to report on duration of gestation, and methods of estimating gestational age have been described in few studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nelson and Ellenberg f 1982) found epileptic women to be just as likely to have increased vaginal bleeding during the first as in the third trimester. Not surprisingly, anemia has been described twice as often in women with epilepsy (Svigos, 1984). Hyperemesis gravidarum occurs more frequently in these patients (Bjerkdal and Bahna, 1973;Nelson and Ellenberg, 1982), which may complicate compliance with oral medication.…”
Section: Complications Of Pregnancymentioning
confidence: 99%
“…It differs from other hemorrhagic disorders in infancy in that the bleeding tends to occur internally during the first 24 h of life. First described by van Creveld (1957) and delineated as a syndrome by Mountain et al (1970), it was initially thought to be associated with exposure to phenobarbital or primidone, but has subsequently been described in children exposed to phenytoin, carbamazepine, diaze- Janz, 1964Speidel and Meadow, 1972Bjerkdal and Bahna, 1973Fedrick, 1983Higgins and Comerfond, 1974Knight and Rhind, 1975Nakane, 1979Nakane et al, 1980Nelson and Ellenberg, 1982Svigos, 1984Kalen, 1986 6 , 1991 pam, mephobarbital, amobarbital, and ethosuximide. Prevalence figures are as high as 30% but appear to average 10%.…”
Section: Hemorrhagic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy represents one of the most frequent chronic neurological conditions, and its prevalence among pregnant women ranges from 0.3 to 0.6% [1][2][3][4][5][6] . Epilepsy be- [16] , daily doses and balancing the plasma levels of free fraction [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%